Model Berbasis Copula untuk Estimasi Kerugian Agregat dalam Asuransi Kecelakaan Lalu Lintas - Ana Kristiana; Yogo Purwono (IPM2KPE, 2022)
This study aims to determine the copula-based model for estimating aggregate losses in traffic accident insurance. This research method is descriptive quantitative. Determination of the best model and the accuracy of the model is determined based on the Akaike Information Criterion (AIC), the smallest Root Mean Square Error (RMSE), and the Vuong Test. The results of the study, there is a dependency relationship or correlation between the frequency of claims and the severity of claims, so that copula is used to model the frequency of claims with a poison distribution and claim severity with a gamma distribution. In conclusion, the clayton copula model is the best model for estimating aggregate losses at the insurance company PT XYZ in the future. Keywords: Insurance, Loss, Correlation, Copula